2021
DOI: 10.15294/jhe.v6i2.42869
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Towards COVID-19 among North Sulawesi Indonesia Residents

Abstract: Background: Coronavirus Disease 2019 (COVID-19) was declared a global pandemic by WHO. To prevent theCOVID-19 transmission is depend on community compliance with health protocols. Public compliance in implementing health protocols during the new normal period is closely related to the Knowledge, Attitudes, and Practices (KAP) about COVID-19.Method: A cross-sectional online survey was used to survey the people of North Sulawesi Indonesia. Data were collected from September 17 to September 30, 2020, with 705 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Research from North Sulawesi Indonesia revealed that most respondents had good knowledge, positive attitudes, and good practices toward COVID-19 prevention. However, knowledge of specific topics is still insufficient (Simanjorang et al, 2021). This present study revealed that Knowledge (adjOR = 2.034,, P = 0.004) and Perception (adjOR = 4.064, 95%CI 1.859 -8.882, P = <0 .001) were possibly associated with behaviors of implementing COVID-19 prevention protocols among communities in Central Java Province.…”
Section: Discussionmentioning
confidence: 59%
“…Research from North Sulawesi Indonesia revealed that most respondents had good knowledge, positive attitudes, and good practices toward COVID-19 prevention. However, knowledge of specific topics is still insufficient (Simanjorang et al, 2021). This present study revealed that Knowledge (adjOR = 2.034,, P = 0.004) and Perception (adjOR = 4.064, 95%CI 1.859 -8.882, P = <0 .001) were possibly associated with behaviors of implementing COVID-19 prevention protocols among communities in Central Java Province.…”
Section: Discussionmentioning
confidence: 59%
“…The results of the field findings above are in accordance with policy evaluation theory, which, according to its definition, is a systematic approach to assessing and analyzing the success, effectiveness, and impact of a policy. Several basic principles can be identified that form the basis of the policy evaluation process (Simanjorang et al, 2021). These principles include:…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge factor indicates a person's attitude regarding Covid-19. Based on Simanjorang et al, (2021) and Limbong et al, (2021) that good knowledge will have a good attitude and good behavior in responding to the Covid-19 disease.…”
Section: Resultsmentioning
confidence: 99%